Thematic Issue Presentation: Critical perspectives in social innovation, social enterprise and/or the social solidarity economy - Bull, Michael; Curtis, Timothy; Nowak, Vicky (NOvation — Critical Studies of Innovation, 2023)
This Thematic Issue seeks to explore critical perspectives of an international nature on social innovation (SI), social enterprise (SE) and/or social solidarity economy (SSE). The aim is to examine the grand narrative, explore the ontological assumptions of the field, challenge the normative and present alternatives that draw attention to political economy, critical theory and critical management studies. Critical perspectives emerged in social innovation (SI) literature as a concerted effort sometime in 2008. A few voices sounded from the edges of the field much earlier. Ash Amin, Professor of Geography at Durham University, inspected the new favourite of public policy way back in 2002, discarded it as a “a poor substitute for a welfare state” and never returned to the subject. There were heated debates that challenged the grand narrative of SI at the International Social Innovation Research Conferences (ISIRC) (once called the Social Enterprise Research Conference before becoming ISIRC with the involvement of the social innovation theme from Skoll Centre). The Voluntary Sector Studies Network (VSSN) conferences picked away at the promise of unlimited performance and achievement of the upstart SE in a mature voluntary and charity network (Aiken, 2002, 2006, 2007; Grenier, 2009; Pharaoh, Scott & Fisher, 2004). Still, on the whole, the literature in the last twenty years has been overwhelmingly interested in promoting social enterprise (SE) and SI as (a) an inherently good thing, (b) a solution to all problems and (c) a politically neutral complement to neo-liberal economics globally. We hope this Thematic Issue raises some interest and some thought-provoking conversations in the future. Many thanks to the reviewers, the authors and above all the editors of NOvation, for trusting us with this Thematic Issue! We hope scholars enjoy the edition as much as we have in bringing this together.